6(x+2)=2(3x+2)+8

Simple and best practice solution for 6(x+2)=2(3x+2)+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+2)=2(3x+2)+8 equation:


Simplifying
6(x + 2) = 2(3x + 2) + 8

Reorder the terms:
6(2 + x) = 2(3x + 2) + 8
(2 * 6 + x * 6) = 2(3x + 2) + 8
(12 + 6x) = 2(3x + 2) + 8

Reorder the terms:
12 + 6x = 2(2 + 3x) + 8
12 + 6x = (2 * 2 + 3x * 2) + 8
12 + 6x = (4 + 6x) + 8

Reorder the terms:
12 + 6x = 4 + 8 + 6x

Combine like terms: 4 + 8 = 12
12 + 6x = 12 + 6x

Add '-12' to each side of the equation.
12 + -12 + 6x = 12 + -12 + 6x

Combine like terms: 12 + -12 = 0
0 + 6x = 12 + -12 + 6x
6x = 12 + -12 + 6x

Combine like terms: 12 + -12 = 0
6x = 0 + 6x
6x = 6x

Add '-6x' to each side of the equation.
6x + -6x = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 0.4(2-x)-(x+3)= | | 7x/3/8=6x-5/8 | | t+1/2=2t-3/6 | | 2=56-9t | | -35+4/15 | | 13x+30=23x-15 | | 0.35s+0.6(30-s)=0.45(30) | | 26-9x=3x-1 | | 9-6x/7=16 | | 12(3x+3)-7(2x-6)=2x-42 | | 6-3x-5x-10x+18-12= | | p-16=51 | | -7/2*10 | | 2(5x-3)-2x-4=5-(6x+1) | | -9-6x/7=16 | | 0.20x+0.05(10-x)=0.10(14) | | -27=n-20 | | 14-3(x-2)=x+16 | | 2a+7=50 | | -7/2-1/4 | | -7/10t=1/8 | | (43-7x)+(83-11x)=(117-22x) | | x^2-12x-16=0 | | c+160=1780 | | c=1/2(s+b)2 | | 0.8(x+4)-0.3x=1.7 | | (x-4)(x+2)(x+2)=0 | | 4(x+8)=-4(x-4) | | 3k+k-4/9=1/3 | | 2x+4-5(x+1)=4x+5 | | x^4/3=1296 | | -x^2+17x+45=0 |

Equations solver categories